Advances in research on fertilization management of vegetable crops - Tei, F.; Nicola, S.; Benincasa, P. (Springer, 2017)
This book is a review of the recent literature on the key scientific and technical subjects of fertilization management in vegetable crops. In the last decades, research on fertilization management in vegetables was aimed at producing economical yields with reduced fertilizer inputs by the development and implementation of cropping systems, nutrient management approaches and crop varieties. Examples of the interventions in cropping systems included adequate crop rotations, inter-cropping, double cropping, and other strategies for a better soil organic matter management; nutrient management approaches included modelling, Decision Support Systems, crop nutritional status testing and precision agriculture technologies; amelioration of crop varieties has been directed toward higher nutrient/fertilizer use efficiency.
Includes index.
Keywords: Vegetables -- Fertilizers.; elektronické knihy; electronic books